2020
DOI: 10.21203/rs.3.rs-35809/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coronavirus Pandemic vs. Temperature in the context of Indian Subcontinent – A preliminary statistical analysis

Abstract: The novel coronavirus (COVID-19) has unleashed havoc across different countries and was declared a pandemic by the World Health Organization. Since certain evidences indicate a direct relationship of various viruses with the weather (temperature in particular), the same is being speculated about COVID-19; however, it is still under investigation as the pandemic is advancing the world over. In this study, we tried to analyze the spread of COVID-19 in the Indian sub-continent with respect to the local temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Temperature doesn't directly affect the number of cases. Significant relationship of negative correlation between the average environmental temperature and exponential growth rates of the infected cases (8) . However, some of the limitations should be noted.…”
Section: Discussion-mentioning
confidence: 94%
“…Temperature doesn't directly affect the number of cases. Significant relationship of negative correlation between the average environmental temperature and exponential growth rates of the infected cases (8) . However, some of the limitations should be noted.…”
Section: Discussion-mentioning
confidence: 94%
“…To address this, we present an integrated COVID-19 risk assessment and mapping (CRAM) framework, wherein we used hazard and vulnerability parameters linked with the COVID-19 contagion, to identify the areas that are under different levels of risk. COVID-19 risk (C19Ri) indicators have been proposed based on the current knowledge of the disease infection, lethality, and spread 25 . The results of the assessment identi ed areas that are under very high-risk category, e.g., NE and SE zone wards of the JMC, Jaipur India.…”
Section: Conclusion and Limitationsmentioning
confidence: 99%
“…Though from observations, it has been found that specific age-groups and people that already have certain pulmonary and cardiovascular issues are particularly more vulnerable to the lethality of this virus (Santesmasses et al 2020). Even the environmental factors such as temperature are not showing any significant role in restricting the spread of this virus in India (Meraj et al 2020). Worldwide, people dying from this disease as of 24 June 2020 are 480210, and confirmed positive cases have reached to 9,376,431.…”
Section: Introductionmentioning
confidence: 99%